PENGARUH LITERASI KEUANGAN DAN RISIKO PENGGUNAAN TERHADAP MINAT BERTRANSAKSI MENGGUNAKAN MOBILE BANKING PADA SISWA/I SMK NEGERI 25 JAKARTA - Anggraeni, Saskia Frila; Budiasih, Yenny; Mahroji, Dwi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2025)
This study aims to explore the influence of financial literacy and risk of use on the interest in transacting using mobile banking among students of SMK Negeri 25 Jakarta. The methodology applied in this study is quantitative using multiple linear regression analysis, involving 65 respondents from class XI of the Accounting, MPLB, and Digital Business study programs. The results showed that financial literacy did not have a significant influence on transaction interest (sig. 0.899 > 0.05), while the risk of use showed a significant influence (sig. 0.000 F table 13.667) with a contribution of 30.6%, while the rest was influenced by other factors that were beyond the limits of this study. Keywords : Financial Literacy, Risk Of Use, Interest in transactions